Influence of Different Apical Preparations on Root Canal Cleanliness in Human Molars: a SEM Study - Gianluca Plotino; Luigi Tocci; Luca Testarelli; Gianluca Gambarini (Stilus Optimus, 2014)
Objectives: To compare the influence of type and dimensions of the apical preparation on the cleanliness of the apical area in molars. Material and Methods: A total of 120 root canals (MB and DB root canals from 30 maxillary molars and mesial root canals from 30 mandibular molars) were instrumented with Mtwo NiTi rotary instruments to a size 25/0.06 taper and were equally divided into three different experimental groups depending on the subsequently apical root canal preparation: Group 1: no further apical preparation, Group 2: apical preparation with Mtwo files to a size 40/0.04 taper, Group 3: apical preparation with Mtwo Apical Files. All root canals were observed through scanning electron microscopy (SEM). Presence of superficial debris and smear layer was evaluated using a score system. Data were statistically analysed using the Kruskal-Wallis and Bonferroni tests with a level of significance set at P < 0.05. Results: Kruskal-Wallis test revealed no differences among groups in the middle and coronal third (P > 0.05), while at the apical level, there was a significant difference for both residual debris and presence of smear layer between Group 1 and both Group 2 (P = 0.003 and P = 0.014) and 3 (P = 0.012 and P = 0.021), while no difference was present between Group 2 and Group 3 (P = 0.871 and P = 0.923). Conclusions: Cleanliness of the apical third in terms of debris and smear layer was statistically better when an apical preparation was performed to a size 40/0.04 taper or with the use of the Mtwo Apical Files.